Luteolin-rich fraction from Perilla frutescens seed meal inhibits spike glycoprotein S1 of SARS-CoV-2-induced NLRP3 inflammasome lung cell inflammation via regulation of JAK1/STAT3 pathway: A potential anti-inflammatory compound against inflammation-induced long-COVID - Dissook, Sivamoke; Umsumarng, Sonthaya; Mapoung, Sariya; Semmarath, Warathit; Arjsri, Punnida; Srisawad, Kamonwan; Dejkriengkraikul, Pornngarm (Frontiers in Medicine, 2023)
Objective The multi-systemic inflammation as a result of COVID-19 can persevere long after the initial symptoms of the illness have subsided. These effects are referred to as Long-COVID. Our research focused on the contribution of the Spike protein S1 subunit of SARS-CoV-2 (Spike S1) on the lung inflammation mediated by NLRP3 inflammasome machinery and the cytokine releases, interleukin 6 (IL-6), IL-1beta, and IL-18, in lung epithelial cells. This study has attempted to identify the naturally- occurring agents that act against inflammation-related long-COVID. The seed meal of Perilla frutescens (P. frutescens), which contains two major dietary polyphenols (rosmarinic acid and luteolin), has been reported to exhibit anti-inflammation activities. Therefore, we have established the ethyl acetate fraction of P. frutescens seed meal (PFEA) and determined its anti-inflammatory effects on Spike S1 exposure in A549 lung cells. Methods PFEA was established using solvent-partitioned extraction. Rosmarinic acid (Ra) and luteolin (Lu) in PFEA were identified using the HPLC technique. The inhibitory effects of PFEA and its active compounds against Spike S1-induced inflammatory response in A549 cells were determined by RT-PCR and ELISA. The mechanistic study of anti-inflammatory properties of PFEA and Lu were determined using western blot technique. Results PFEA was found to contain Ra (388.70 ± 11.12 mg/g extract) and Lu (248.82 ± 12.34 mg/g extract) as its major polyphenols. Accordingly, A549 lung cells were pre-treated with PFEA (12.5-100 μg/mL) and its two major compounds (2.5-20 μg/mL) prior to the Spike S1 exposure at 100 ng/mL. PFEA dose-dependently exhibited anti-inflammatory properties upon Spike S1-exposed A549 cells through IL-6, IL-1β, IL-18, and NLRP3 gene suppressions, as well as IL-6, IL-1β, and IL-18 cytokine releases with statistical significance (p < 0.05). Importantly, Lu possesses superior anti-inflammatory properties when compared with Ra (p < 0.01). Mechanistically, PFEA and Lu effectively attenuated a Spike S1-induced inflammatory response through downregulation of the JAK1/STAT3-inflammasome-dependent inflammatory pathway as evidenced by the downregulation of NLRP3, ASC, and cleaved-caspase-1 of the NLRP3 inflammasome components and by modulating the phosphorylation of JAK1 and STAT3 proteins (p < 0.05). Conclusion The findings suggested that luteolin and PFEA can modulate the signaling cascades that regulate Spike S1-induced lung inflammation during the incidence of Long-COVID. Consequently, luteolin and P. frutescens may be introduced as potential candidates in the preventive therapeutic strategy for inflammation-related post-acute sequelae of COVID-19.